Assessing the effect of interspecies oocyte nucleolar material dosage on embryonic development - Benc, Michal; Martinkova, Stanislava; Rychtarova, Jana; Fulka, Josef; Bartkova, Alexandra; Fulka, Helena; Laurincik, Jozef (Theriogenology, 2020)
Sequence differences are considered to be the basic cause of developmental failure in interspecies embryos when more distant species are combined. However, other phenomena, such as insufficient or excessive quantity of specific cellular factors, might also influence the outcome. These effects are usually not considered. One of the organelles shown to contain different amount of proteins is the oocyte nucleolus-like body. Here we show that upon interspecies transfer, a single porcine nucleolus-like body is unable to support the development of a mouse parthenogenetic embryo derived from an enucleolated oocyte. However, when the amount of the porcine nucleolar material is increased to equalize the amount of mouse nucleolar material by transferring two nucleolus-like bodies, mouse embryos are able to pass the developmental block elicited by enucleolation. These embryos progress to the blastocyst stage at rates comparable to controls. Thus, using the model of an interspecies nucleolus-like body transplantation between mouse and pig oocytes, we show that an inadequate amount of nucleolar factors, rather than the species origin, affects the development. In a wider context of interspecies nuclear transfer schemes, the observed incompatibility between more distant species might not stem simply from sequence differences but also from improper dosage of key cellular factors.
Keywords: Embryonic Development; Embryo; Nuclear Transfer Techniques; techniky jaderného přenosu; těhotenství; Oocyte; buněčné jadérko; Nucleolus; Mice; Interspecies transfer; Enucleolation; Swine; Oocytes; ženské pohlaví; zvířata; oocyty; Pregnancy; embryonální vývoj; myši; prasata; Blastocyst; Cell Nucleolus; Female; blastocysta; Animals